ANALISIS YURIDIS TINDAK PIDANA PEMBUNUHAN ANAK OLEH IBUNYA YANG MASIH DIBAWAH UMUR (Studi Kasus Putusan 1/Pid.Sus-Anak/2024/PN Mtp) - Fahlevie, Rinaldi Agusta; Verawati, Verawati; Istiqomah, Istiqomah (IUS FACTI : Jurnal Berkala Fakultas Hukum Universitas Bung Karno, 2024)
Abstrak : Penelitian ini mengetahui bagaimana penerapan terhadap tindak pidana pembunuhan yang dilakukan oleh ibunya yang masih berusia anak dibawah umur. Dengan mempergunakan dasar hukum Undang-Undang perlindungan anak sebagaimana terkahir diubah untuk kedua kalinya dengan Undang-Undang Republik Indonesia Nomor 17 Tahun 2016 tentang Penetapan Peraturan Pemerintah Pengganti UndangUndang Nomor 1 Tahun 2016 tentang Perubahan Kedua Atas Undang- Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak dikaitkan dengan Penggunaan ketentuan Pasal 341 KUHP.Penelitian ini menggunakan pendekatanstudi kasus dan hukum normatif yang bersifat deskriptif, dengan menggunakan data sekunder yang bersumber dari bahan hukum primer dan bahan hukum sekunderPenerapan Tindak Pidana Terhadap Pelaku Penyembunyian Mayat Bayi Dengan Maksud Menutupi Kelahirannya dengan maksud menutupi kelahirannya dapat dikenakan pasal 341 KUHP atau tentang kekerasan terhadap anak yakni diatur dalam Pasal 80 Ayat (3) dan (4) jo pasal 76C Undang-Undang Republik Indonesia Nomor 35 Tahun 2014 .Didalam perkara Pengadilan Negeri Martapura majelis hakim sebagaimna perkara Putusan 1/Pid.Sus- Anak/2024/PN Mtp lebih memilih untuk memutuskan terdakwa kepada ketentuan pasal Pasal 341 KUHP, dibandingkan dengan ketentuan Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak , walaupun Undang perlindungan anak lebih spesialis akan tetapi dengan memtimbang rasa keadilan dan tujuan pemidanaan yang terbaik untuk Anak Yang Berhadapan dengan Hukum sudah tepat sebagaimana ketentuan filosofi dibuatnya Undang-Undang Nomor 11 Tahun 2012 tentang sistem peradilan anak.Kata Kunci : Tindak Pidana, Anak, Ibu.Abstract : This research finds out how the crime of murder is applied to a mother who is still a minor. By using the legal basis of the Child Protection Law as last amended for the second time by Law of the Republic of Indonesia Number 17 of 2016 concerning the Determination of Government Regulations in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection in relation to by using the provisions of Article 341 of the Criminal Code.This research uses a case study approach and descriptive normative law, using secondary data sourced from primary legal materials and secondary legal materials. The application of criminal acts against perpetrators of hiding baby corpses with the intention of covering up their birth. With the intention of covering up their birth, they can be subject to Article 341 of the Criminal Code or regarding violence. against children, namely regulated in Article 80 Paragraphs (3) and (4) in conjunction with Article 76C of Law of the Republic of Indonesia Number 35 of 2014. In the Martapura District Court case, the panel of judges as in the case of Decision 1/Pid.Sus-Anak/2024/PN Mtp prefer to decide on the defendant according to the provisions of Article 341 of the Criminal Code, compared to the provisions of Law Number 23 of 2002 concerning Child Protection, although the child protection law is more specialist, but taking into account the sense of justice and the aim of the best punishment for children in conflict with the law is in accordance with the philosophical provisions of Law Number 11 of 2012 concerning the juvenile justice system.AbstractThis research finds out how the crime of murder is applied to a mother who is still a minor. By using the legal basis of the Child Protection Law as last amended for the second time by Law of the Republic of Indonesia Number 17 of 2016 concerning the Determination of Government Regulations in Lieu of Law Number 1 of 2016 concerning the Second Amendment to Law Number 23 of 2002 concerning Child Protection in relation to by using the provisions of Article 341 of the Criminal Code. This research uses a case study approach and descriptive normative law, using secondary data sourced from primary legal materials and secondary legal materials. The application of criminal acts against perpetrators of hiding baby corpses with the intention of covering up their birth. With the intention of covering up their birth, they can be subject to Article 341 of the Criminal Code or regarding violence. against children, namely regulated in Article 80 Paragraphs (3) and (4) in conjunction with Article 76C of Law of the Republic of Indonesia Number 35 of 2014. In the Martapura District Court case, the panel of judges as in the case of Decision 1/Pid.Sus-Anak/2024/PN Mtp prefer to decide on the defendant according to the provisions of Article 341 of the Criminal Code, compared to the provisions of Law Number 23 of 2002 concerning Child Protection, although the child protection law is more specialist, but taking into account the sense of justice and the aim of the best punishment for children in conflict with the law is in accordance with the philosophical provisions of Law Number 11 of 2012 concerning the juvenile justice system.Keywords: Crime, Children, Mother.